Sosialisasi dan Pelatihan Perhitungan PPh Pasal 21 Menurut UU Harmonisasi Peraturan Perpajakan Pada Sekolah TK ABA’Aisyiyah - Sri Setia Ningsih; Roosita Meliani; Aam Aminah; Lestari Adhi Widyowati; Yumniati Agustina (Medan Resource Center, 2022)
Tax is one source of government funds used for development. The benefits of the tax cannot be felt directly by the taxpayers, but the funds collected from this tax will be used for development evenly for the public interest. To broaden the tax base, recently the government reformed the taxation system through the Law on Harmonization of Tax Regulations (UU HPP). The purpose of this law is to increase taxpayer compliance which is considered by the government to be very low. This is due to a lack of knowledge and information about taxes which results in low awareness of taxpayers. To increase knowledge and information, socialization and training are needed which in this case are focused on Income Tax Article 21, namely withholding taxes on income in the form of salaries, wages, honoraria, benefits and other payments received by employees, non-employees, former employees, severance pay recipients and others. so. The service was carried out at the ABA Kindergarten School, 'Aisyiyah PCA East Ciputat, South Tangerang City. The method used in this community service is the lecture, practice and discussion method which is expected to increase the understanding of educators regarding Income Tax Article 21. Through the evaluation of the results of the pre test and post test it shows that the level of understanding before training is held on average is 17%. Then, after the implementation of socialization and training, the average percentage of participants who answered correctly was 96%. Based on these results it can be said that the participants had quite a big change in understanding their tax knowledge, especially how to calculate Article 21 Income Tax and the adjustments to calculate it according to the HPP Law.